European Prevention of Alzheimer's Dementia Registry: Recruitment and prescreening approach for a longitudinal cohort and prevention trials. Issue 6 (28th March 2018) - Vermunt, Lisa; Veal, Colin D.; ter Meulen, Lea; Chrysostomou, Charalambos; van der Flier, Wiesje; Frisoni, Giovanni B.; Guessous, Idris; Kivipelto, Miia; Marizzoni, Moira; Martinez‐Lage, Pablo; Molinuevo, José Luis; Porteous, David; et al.
Abstract: Introduction: It is a challenge to find participants for Alzheimer's disease (AD) prevention trials within a short period of time. The European Prevention of Alzheimer's Dementia Registry (EPAD) aims to facilitate recruitment by preselecting subjects from ongoing cohort studies. This article introduces this novel approach. Methods: A virtual registry, with access to risk factors and biomarkers for AD through minimal data sets of ongoing cohort studies, was set up. Results: To date, ten cohorts have been included in the EPAD. Around 2500 participants have been selected, using variables associated with the risk for AD. Of these, 15% were already recruited in the EPAD longitudinal cohort study, which serves as a trial readiness cohort. Discussion: This study demonstrates that a virtual registry can be used for the preselection of participants for AD studies.